The authenticity of the letter of ‘Abd Allâh b. Ibâḍ to ‘Abd al-Malik - Wilferd Madelung (Revue des Mondes Musulmans et de la Méditerranée)
The so-called first letter of Ibn Ibâḍ was long considered in modern scholarship as an authentic letter of ‘Abd Allâh b. Ibâḍ, the reputed founder of the Ibâḍiyya sect, to the Umayyad caliph ‘Abd al-Malik. This was questioned first by John Wilkinson and then by Michael Cook in his book on Early Muslim Theology, who proposed that the letter was written rather by Jâbir b. Zayd to the Muhallabid amîr ‘Abd al-Malik b. al-Muhallab. In his recent book on Ibadism, John Wilkinson has argued that the letter was addressed to ‘Abd al-Malik, the son of the caliph ‘Umar II, and that Jâbir b. Zayd could not have been its author. It will be argued in this paper that the letter is an authentic letter of ‘Abd Allâh b. Ibâḍ addressed to the son of ‘Umar II. Ibn Ibâḍ was not the founder of the Ibâḍiyya sect, but rather a contemporary and rival of Abû ‘Ubayda Muslim b. Abî Karîma.